Non-motorised transport prioritisation model using spatial intelligence - Poyil, Rohith P. (2020)
The aim of the work reported in this paper was to develop a non-motorised transport (NMT, covering walking and cycling) prioritisation model using a geographic information system that can be used for planning as well as auditing existing NMT infrastructure. ArcGIS 10.1 ModelBuilder software was used to design NMT prioritisation using the cases of Sembawang and Yishun residential townships in Singapore. The concept of spatial intelligence was used to predict the NMT prioritisation scheme; spatial intelligence is the ability to visualise spatial features and apply spatial judgement for mobility problems involving navigation or to identify fine details or patterns. The NMT prioritisation model was developed based on NMT movements in relation to spatial features such as residential buildings, community centres, schools and hospitals, recreation and sports centres, economic zones, transport hubs, bus stops and green spaces. The designed NMT prioritisation map is the weighted sum of Euclidean distance rasters of eight spatial layers. The results were subsequently used to assess the existing NMT facilities in the Sembawang and Yishun townships.